Kajian Psikolinguistik dalam Penguasaan Kosa Kata Bahasa Jepang Mahasiswa Program Studi Sastra Jepang Universitas Udayana - Lestari, Ni Putu Candra; Damayanti, Silvia; Andry Anita Dewi, Ni Made (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang; Vol 5 No 2 (2023)DO - 10.24843/JS.2023.v05.i02.p12, 2023)
Psycholinguistics is related to three things, namely language comprehension , language production , and language acquisitio n . One of the goals of language acquisition studies is to facilitate the process of language acquisition, including foreign languages, for example Japanese. The dimension of acquiring Japanese is closely related to learning Japanese and mastering it. One of the basic things in mastering Japanese is vocabulary mastery. Vocabulary mastery reflects mastery of reading, writing, listening, and speaking skills. This study describes an evaluation of students' Japanese vocabulary mastery, as well as the potential for mastery associated with the six dimensions of language acquisition by Klein (1986). The main subjects of this research are all active students of the Japanese study program at Udayana University starting from the 2018 to 2021 class, totaling 258 people. Data were collected by the test method, where students worked on questions about knowledge of Japanese vocabulary which included competency components according to international standards of Japanese language skills, namely on the fulfillment of eight indicators of vocabulary knowledge tested, namely: reading Kanji; write Kanji characters; determine vocabulary according to context; determine synonyms; use words in sentences; determine the correct form of the word; compose sentences; and determine connecting words in a discourse.   Data were analyzed descriptively qualitatively. The research resulted in an evaluation that the level of students' Japanese language proficiency was 54%. It is necessary to hold reading and writing exercises as a follow-up step. Regarding the potential for students' mastery of Japanese, the propensity and access factors are very important to improve.